Effects of acupuncture on quality of life and pain in patients with osteoporosis—a pilot randomized controlled trial. Issue 1 (December 2016) - Schiller, Joerg; Korallus, Christoph; Bethge, Matthias; Karst, Matthias; Schmalhofer, Marie-Lena; Gutenbrunner, Christoph; Fink, Matthias
Abstract Summary In this sham-controlled study, 53 patients received 10 sessions of acupuncture treatment over 5 weeks to investigate the effects of acupuncture on the pain and quality of life of patients with osteoporosis. The results showed significant favorable effects of verum acupuncture on quality of life. Both interventions showed sustained and clinically relevant effects on pain. Purpose Standard analgesic treatment is associated with adverse events in patients with osteoporosis, especially elderly and/or comorbid patients. As acupuncture has gained widespread acceptance as a complementary treatment modality with few side effects, the aim of this study was to evaluate the effects of acupuncture on the pain and quality of life of patients with osteoporosis. Methods In total, 53 patients with vertebral compression fractures, osteoporosis-associated spinal deformities, and resultant pain were randomly allocated to the verum acupuncture with deep needling of specific points following the principles of traditional Chinese medicine (n  = 29) or control acupuncture group with superficial needling of non-acupuncture points (n  = 24). All patients received 10 sessions of standardized verum or control acupuncture treatment over 5 weeks. Pain (VAS score 1–100) and quality of life (QUALEFFO-41) were measured at the start of treatment (T0), before each acupuncture session (T1), and at 1 (T2) and 3 months (T3) post-treatment. Results Both acupuncture treatments significantly reduced activity-related pain and pain at rest over time. The verum acupuncture group experienced a significantly greater reduction in mean pain intensity at rest than the control group. In the control group, quality of life improved only temporarily post-treatment (T2) and slightly declined at the end of the follow-up period (T3). In contrast, patients in the verum acupuncture group experienced continuous and significant improvements in quality of life up to 3 months after treatment (T3). Conclusions Both types of acupuncture were equally effective in producing sustained, clinically relevant pain relief in patients with osteoporosis. Verum acupuncture had stronger and longer-lasting effects on quality of life and pain at rest. The possible reasons for these findings include the specificity of acupuncture point selection and the performance of needle stimulation.